CLAM FISHERY OF MULKY ESTUARY DURING 1978-1982 - Rao, G Syda (Indian Journal of Fisheries, 2011)
The magnitude of production of and effort spent in the clam fishery ofMulky estuary from 1978-79 to 1981-82 are presented. An estimated averageof about 475 t of clams were landed annually, comprising Meretrix casta (76%)and Paphia malabarica (24%). M. casta is utilised for its meat and shells,whereas P. malabrica exclusively for its meat. The methods of fishing, utilisationand price structure are indicated. Heavy precipitation during S.W. monsoonappears to influence the clam fishery in the succeeding months